Thrombembolic complications after total ankle replacement - Barg, Alexej (Springer US, 2013)
The literature addressing functional outcome and survivorship of prosthesis components is constantly growing. However, the data on thromboprophylaxis and thrombembolic complications in patients who underwent TAR are scarce. A total of 31 studies were included in the systemic literature review. The incidence of thrombembolic complications varied between 0.0 % and 9.8 %. Most commonly, low molecular weight heparin was used as thromboprophylaxis for 6 weeks postoperatively. The incidence of thrombembolic complications was comparable with that of symptomatic deep vein thrombosis in patients with total knee or hip replacement.